2012
DOI: 10.1111/j.1753-4887.2012.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bread consumption, body weight, and abdominal fat distribution: evidence from epidemiological studies

Abstract: A long-standing belief held by the general public is that bread fattens. This encourages many people to restrict, or even eliminate, bread from their diet. The present review was conducted to assess whether or not eating patterns that include bread are associated with overall obesity or excess abdominal adiposity, whether in the general population or in subjects undergoing obesity management. The literature search included articles published over the past 30 years that focused on dietary patterns that included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
(272 reference statements)
0
24
0
3
Order By: Relevance
“…18,20,21 Removal of bran and germ in the production of refined grains eliminates these health benefits due to the removal of both these components and their synergistic effects. 30 Current trends in scientific studies of whole grain versus refined grain are replete with results showing consistent health-benefiting properties, including lower body fat percentage in postmenopausal women, and in general, in relation to whole grain bread consumption, 19,31 and a lower BMI Z-score in schoolchildren (the BMI Z-score allows for a BMI comparison between a particular child and a group of children of the same age and sex). 24,25 The socio-demographic group that consumes a greater amount of whole grain comprises the more health-conscious segment, which consists of women, older people, and more educated people.…”
Section: Whole Grain Foods and Healthmentioning
confidence: 99%
“…18,20,21 Removal of bran and germ in the production of refined grains eliminates these health benefits due to the removal of both these components and their synergistic effects. 30 Current trends in scientific studies of whole grain versus refined grain are replete with results showing consistent health-benefiting properties, including lower body fat percentage in postmenopausal women, and in general, in relation to whole grain bread consumption, 19,31 and a lower BMI Z-score in schoolchildren (the BMI Z-score allows for a BMI comparison between a particular child and a group of children of the same age and sex). 24,25 The socio-demographic group that consumes a greater amount of whole grain comprises the more health-conscious segment, which consists of women, older people, and more educated people.…”
Section: Whole Grain Foods and Healthmentioning
confidence: 99%
“…However, these relationships have been mainly observed for whole-grain bread or cereals (Gil et al 2011), whereas the associations for white bread are not clear, and have been associated with increased adiposity and weight gain (Bautista-Castano et al 2012a;Bautista-Castano and Serra-Majem 2012b;Williams 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a recent European study found a positive association between white bread intake and an increase in waist circumference (Romaguera et al 2011). A review of 15 worldwide observational studies, including prospective ones (Koh-Banerjee et al 2004;Liu et al 2003), concluded that a high intake of whole grains (about 3 servings per day) is associated with a lower BMI and less central adiposity (Harland and Garton 2008), a conclusion borne out in central obesity studies of fiber (Du et al 2010), whole grain (McKeown et al 2010), and whole-grain bread (Bautista-Castano and Serra-Majem 2012). (Only a more recent British study of 1599 adults 19-64 years of age did not show an association between waist circumference and wholegrain intake (Thane et al 2009). )…”
Section: Discussionmentioning
confidence: 99%